Presentation is loading. Please wait.

Presentation is loading. Please wait.

6. Factorise Expressions

Similar presentations


Presentation on theme: "6. Factorise Expressions"— Presentation transcript:

1 6. Factorise Expressions
Begin to factorise an expression by taking out the common number factors b Factorise an expression by taking out the common number factors a Factorise an expression by taking out the common algebraic factors c Find the values of constants in an identity by factorising 7c Substitute positive and negative numbers into expressions involving small powers and brackets c Reference Material Text book: section 7.5 page 118 MEP: 8.8 section 3

2 Factorise an expression by taking out the common number factors 6a
6a + 12 = 6(a + 2) 5b – 15 = 5(b – 3) 4a + 2b = 2(2a + b) 3x – 2y = 3x – 2y no common factors here  4c – 10t = 2(2c – 5t) 12f + 15 = 3(4f + 5) 9y – 21n = 3(3y – 7n) 5y – 5 = 5(y – 1) 15 – 5p = 5(3 – p)

3 3x + x² = x(3 + x) 4y² - 2y = 2y(2y – 1) 6f² - 3f = 3f(2f – 1)
Factorise an expression by taking out the common algebraic factors 7c 3x + x² = x(3 + x) 4y² - 2y = 2y(2y – 1) 6f² - 3f = 3f(2f – 1) 2f²g + 4fg² = 2fg(f + 2g) 22 May 2019


Download ppt "6. Factorise Expressions"

Similar presentations


Ads by Google